The significant role of mast cells in cancer - Khazaie, Khashayarsha; Blatner, Nichole R.; Khan, Mohammad Wasim; Gounari, Fotini; Gounaris, Elias; Dennis, Kristen; Bonertz, Andreas; Tsai, Fu-Nien; Strouch, Matthew J.; Cheon, Eric; Phillips, Joseph D.; Beckhove, Philipp; et al. (Cancer and metastasis reviews, 2011)
Mast cells (MC) are a bone marrow-derived, long-lived, heterogeneous cellular population that function both as positive and negative regulators of immune responses. They are arguably the most productive chemical factory in the body and influence other cells through both soluble mediators and cell-to-cell interaction. MC are commonly seen in various tumors and have been attributed alternatively with tumor rejection or tumor promotion. Tumor-infiltrating MC are derived both from sentinel and recruited progenitor cells. MC can directly influence tumor cell proliferation and invasion but also help tumors indirectly by organizing its microenvironment and modulating immune responses to tumor cells. Best known for orchestrating inflammation and angiogenesis, the role of MC in shaping adaptive immune responses has become a focus of recent investigations. MC mobilize T cells and antigen-presenting dendritic cells. They function as intermediaries in regulatory T cells (Treg)-induced tolerance but can also modify or reverse Treg-suppressive properties. The central role of MC in the control of innate and adaptive immunity endows them with the ability to tune the nature of host responses to cancer and ultimately influence the outcome of disease and fate of the cancer patient.
Gesehen am 01.08.2022